From improvements in accessibility to the impact on territorial cohesion: the spatial approach - Stępniak, Marcin; Rosik, Piotr (Journal of Transport and Land Use, 2015)
During the last decade, Poland has experienced a big push in road network development. As a result, the fundamentals of the modern road network have been established. This paper aims to recognize the consequences of changes in accessibility for territorial cohesion, analyzed simultaneously in national and international dimensions. The results provided show that similar spatial patterns and the overall scale of improvement in accessibility lead to entirely different impacts on the level of territorial cohesion. From the international perspective, the investments implemented have a strong positive cohesion impact, while from the national perspective a slight increase in regional polarization has been produced. Moreover, there was an adverse effect on territorial cohesion for almost 40 percent of Polish municipalities, depending on whether or not we include international destinations. The fact that analyses conducted in the national and international dimension yielded opposite results supports the presented approach of a multidimensional evaluation of transport network development.